DAYA TERIMA DAN TOTAL COST KOMBINASI SARI KULIT BUAH NAGA MERAH DAN SARI BUAH JAMBU BIJI MERAH - Sari, Syafrina Mareta; Adi, Annis Catur; Andrias, Dini Andrias (Media Gizi Indonesia, 2017)
Antioxidant plays a role as the free radical savaging. The red guava and the red dragon fruit peel contain high antioxidants so it is potentially to be a functional product. The aim of this study was to analyze the effect of red guava juice and red dragon fruit peel essence addition on yoghurt acceptability and total cost. The research used a factorial design of 5 repetitions on 5 formulas. There are 1 control formula (F0) and 4 modiï¬ cation formulas (F1, F2, F4, F5) with the addition of red guava juice and red dragon fruit peel. The panelist on this research consist of 30 untrained panelists. Descriptive analysis and inferential statistic using Friedman and Wilcoxon Sign Rank Test with α = 0,05 were used to analyze the difference of acceptability between the formulas. Panelists showed that the best treatment was F4 yoghurt formula (44% addition of fruit juice with the ratio of guava juice and red dragon fruit peel 50:50) and it has the most preferred acceptability (color, aroma, texture, and taste) with the average value was 2.91 and food cost per serving (100 ml) was Rp 2.900,00. Formula F4 has a good acceptability and lower total cost than commercial yoghurt. This formula has a potential to be an alternative functional drink. The aroma of yoghurt can be increased by eliminate cooking process on the red dragon fruit peel juice. Keywords: acceptability, red guava, red dragon fruit peel, total cost, yoghurt